(untitled) - Pagana, Kathleen Deska (Missouri, 1998)
Completely revised and updated, the 2nd Edition of this bestselling resource offers superb guidance on diagnostic and laboratory testing for health professionals in both academic and clinical settings. Each chapter begins with a list of the tests covered within a particular test type, as well as an overview of that category, including specimen collection techniques. Next, a consistent presentation addresses each test's normal findings, indications, contraindications, potential complications, interfering factors, procedure and patient care, test results and clinical significance, and related tests. Up-to-date, easy-to-use, and in full color, this book covers virtually every clinically significant test, including allergy blood testing, atrial natriuretic factor, homocysteine, N-telopeptide, troponins, and more
Keywords: Diagnosis, Laboratory,Diagnosis, Radioscopic,Chẩn đoán, phòng thí nghiệm,Chẩn đoán, xạ trị